Improving human settlement (Menschliche Siedlungen verbessern). Papers presented at the University of British Columbia between february and may 1976 in preparation for the UN-conference on human settlements Habitat '76. - (:unkn) unknown (My University, 1977)
Die Beiträge der Autoren behandeln Industrie- und Entwicklungsländer. Themen Siedlungspolitik in China - Wie Architekten und Planer Siedlungen beeinflussen usw.
Keywords: Siedlungsplanung; Städtebau; Stadtplanung; Wohnungswesen